Aizkibel's Euzkeratik erderara biurtzeko itztegia: from manuscript to publication - Santazilia, Ekaitz (Fontes linguae vasconum, 2011)
In the world of Basque studies, we rarely have the opportunity to compare the published version and the manuscript of a text: in the case of Aizkibel's Basque-Spanish Dictionary, however, we do. In this article, we compare the manuscript and the version published after the death of the author. Concerning the manuscript, we show that it is the source of the publication and, after dating it, we express our doubts regarding its authorship. We have extracted the most remarkable differences between the publication and the manuscript, in terms of both form and content, and seek a potential justification. Finally, having observed that there are even differences between copies of the publication itself, we investigate the number of editions and try to explain these differences, describing the chronology of the printing and distribution of the dictionary. Adapted from the source document